Novel (±)-trans-β-lactam ureas: Synthesis, in silico and in vitro biological profiling - Jurin Mladenka; Stepanić Višnja; Bojanić Krunoslav; Vadlja Denis; Kontrec Darko; Dražić Tonko; Roje Marin (Acta Pharmaceutica)
A diastereomeric mixture of racemic 3-phthalimido-b-lactam 2a/2b was synthesized by the Staudinger reaction of carboxylic acid activated with 2-chloro-1-methylpyridinium iodide and imine 1. The amino group at the C3 position of the b-lactam ring was used for further structural upgrade. trans-b-lactam ureas 4a–t were prepared by the condensation reaction of the amino group of b-lactam ring with various aromatic and aliphatic isocyanates. Antimicrobial activity of compounds 4a–t was evaluated in vitro and neither antibacterial nor antifungal activity were observed. Several of the newly synthesized trans-b-lactam ureas 4a–c, 4f, 4h, 4n, 4o, 4p, and 4s were evaluated for in vitro antiproliferative activity against liver hepatocellular carcinoma (HepG2), ovarian carcinoma (A2780), breast adenocarcinoma (MCF7) and untransformed human fibroblasts (HFF1). The b-lactam urea 4o showed the most potent antiproliferative activity against the ovarian carcinoma (A2780) cell line. Compounds 4o and 4p exhibited strong cytotoxic effects against human non-tumor cell line HFF1. The b-lactam ureas 4a–t were estimated to be soluble and membrane permeable, moderately lipophilic molecules (logP 4.6) with a predisposition to be CYP3A4 and P-glycoprotein substrates. The tools PASS and SwissTargetPrediction could not predict biological targets for compounds 4a–t with high probability, pointing to the novelty of their structure. Considering low toxicity risk, molecules 4a and 4f can be selected as the most promising candidates for further structure modifications.